Bacterial Communities in the Womb During Healthy Pregnancy - Zhu, Lihong; Luo, Fei; Hu, Wenjing; Han, Yang; Wang, Yuezhu; Zheng, Huajun; Guo, Xiaokui; Qin, Jinhong (Frontiers in Microbiology, 2018)
The idea that healthy uterine cavity is sterile is challenged nowadays. It is still debatable whether the bacteria present in the uterine cavity during pregnancy are residents or invaders. To reveal microbiome composition and its characteristics in the womb of pregnant women, 41 decidual tissue samples and 64 amniotic fluid samples were taken from pregnant Chinese women. DNA extraction was followed by pyrosequencing of the hypervariable V4 region of the 16S rDNA gene to characterize womb microbiome. Both types of samples had low diversity microbiome with Proteobacteria and Enterobacteriaceae being the dominant phylotypes at the phylum and family level respectively. To characterize the nature of colonization during pregnancy, the presence of endogenous biomass was confirmed by cultivation. Surprisingly, all of the 50 amniotic fluid samples studied were culture-negative, whereas 538 out of 1,834 placenta samples were culture-positive. Our results suggested that womb contained microbiome with low diversity. Culture-based investigation of amniotic fluid and placenta samples confirmed the presence of cultivable microorganisms in the placenta but not in amniotic fluid.